Small bowel biopsy. Issue 11 (November 1985) - Collins, A L; Brookfield, D S; Hyde, I; Rolles, C J
Abstract : We describe our technique of small bowel biopsy, which has been used on 190 occasions over a four year period. In 77%, the examination was completed within 10 minutes, and fluoroscopy times were less than 10 seconds in 75% of the cases. The technique is easily taught, and it has made the examination a minor procedure.